Pengaruh Media Tanam Berbahan Dasar Cocopeat Pada Pembibitan Kakao (Theobroma cacao L.) - Vina Ayesta Ardilla; Wilna Sari; Kiki Amelia; Mentari Larashinda (JURNAL AGROPLASMA, 2026)
Cocoa  (Theobroma  cacao  L.)  is  a  plantation  crop  of  high  economic  value  that  requires  high-quality  seedlings  to  support  optimal  field  productivity.  One  of  the  main  constraints  in  cocoa  nurseries,  particularly  for  the  Trinitario  variety  in  Jorong  Kampung  Juar,  Nagari  Tanjung,  is  the  use  of  planting  media  derived  from  burned  soil,  which  is  generally  low  in  nutrients  and  may  contain  potentially  toxic  compounds.  Cocopeat,  a  by-product  of  coconut  husk  processing,  has  potential  as  an  alternative  growing  medium  due  to  its  physical  properties,  including  high  water-holding  capacity,  improved  aeration,  and  a  pH  suitable  for  cocoa  growth.  This  study  aimed  to  evaluate  the  effects  of  different  cocopeat-based  growing  media  compositions  on  the  growth  of  cocoa  seedlings  and  to  assess  their  suitability  as  an  alternative  nursery  medium.  The  study  employed  a  Completely  Randomized  Design  (CRD)  with  four  treatments  and  five  replications.  The  treatments  consisted  of  soil  and  goat  manure  as  the  control,  and  three  cocopeat  application  rates  of  450  g,  550  g,  and  650  g  per  polybag.  Observed  parameters  included  plant  height,  number  of  leaves,  stem  diameter,  growing  media  temperature,  growing  media  pH,  leaf  color,  and  plant  survival  percentage.  Data  were  analyzed  using  analysis  of  variance  (ANOVA),  and  the  coefficient  of  variation  was  used  to  evaluate  data  homogeneity  and  experimental  precision.  The  results  showed  that  the  application  of  cocopeat  at  different  rates  did  not  significantly  affect  any  of  the  observed  growth  parameters  of  cocoa  seedlings.  Nevertheless,  a  positive  growth  trend  was  observed  in  several  vegetative  parameters  in  treatments  containing  cocopeat,  particularly  in  maintaining  stable  moisture,  temperature,  and  pH  of  the  growing  media.  The  low  coefficients  of  variation  across  most  parameters  indicated  that  the  data  were  homogeneous  and  the  experiment  had  a  high  level  of  reliability.  All  treatments  resulted  in  a  100%  survival  rate,  indicating  that  cocopeat-based  growing  media  are  safe  and  suitable  for  cocoa  seedling  production.  Therefore,  cocopeat  can  be  used  as  an  alternative  growing  medium  for  cocoa  nurseries,  although  adjustments  in  composition  are  necessary  to  optimize  its  benefits  under  local  condition. Keywords:  cocoa  seedlings,  cocopeat, cocoa, vegetative